Work-life interface and intention to stay in the midwifery profession among pre- and post-clinical placement students in Canada - Farimah HakemZadeh; Elena Neiterman; James Chowhan; Jennifer Plenderleith; Johanna Geraci; Isik Zeytinoglu; Derek Lobb (BMC, 2020)
Abstract Background Midwifery students' intention to stay in the profession can be influenced by how the interface of their work and personal life is affected by their clinical placement experience. The purpose of this study is to compare the intention to stay in the midwifery profession and its association with three work/personal life interface constructs among pre- and post-clinical placement midwifery students in Canada. The constructs investigated are work interference with personal life, personal life interference with work, and work/personal life enhancement. Methods Quantitative cross-sectional data were collected through two separate online surveys completed by pre- and post-clinical placement students. In total, 456 midwifery students attending six different midwifery education programs responded to the surveys. Results Compared to pre-clinical placement students, post-clinical placement students had significantly lower intention to stay in the profession. For pre-clinical placement students, higher personal life interference with work was significantly associated with lower intention to stay in the profession. For post-clinical placement students, higher work interference with personal life was associated with lower intention to stay in the profession. We did not find any significant relationships between work/personal life enhancement and intention to stay in the profession in pre- or post-clinical placement students. Conclusion Pre- and post-clinical placement students have different intentions to stay in the profession. For pre-clinical placement students, those who report that their personal lives highly interfere with work are less likely to want to stay in the midwifery profession. Post-clinical placement students reported that when working interfered with their personal lives they were less likely to want to stay in the profession. Our findings highlight the importance of offering students a realistic preview of the required commitment, workload, and personal involvement in the midwifery profession prior to applying or accepting a spot in a midwifery education program. Furthermore, facilitating the development of skills to better manage the expectations in midwifery work and personal lives might help with maintaining positive intentions to stay in the profession.